Labor trajectory of sociologists in times of change and conflict - Vargas Morales, Zenón Eduardo (2018)
Sociology as a profession has its beginnings from its professionalization in the 1960s, in which the theoretical, methodological and instrumental foundations are laid down, which guarantees its relevance and continuity as a social science. In this article, which is part of a forthcoming book, it is presented about the work history of sociologists in times of change and conflict, where the following research question is posed: How has the work experience of the Sociologists in times of change and conflict? The objective is to know the work trajectory from the 1960s to the present, in addition to highlighting the family background to understand intergenerational mobility through their educational and work level.